Differences in Levels of Placenta Growth Factor in The Vitreous After Administration of Aflibercept Compared to the Control Group of Proliferative Diabetic Retinopathy - Arnila Novitasari Saubig; Arief Wildan; Afrisal Hari Kurniawan (Majalah Oftalmologi Indonesia, 2017)
Introduction: to compare the levels of Placenta Growth Factor in the vitreous on patients with proliferative diabetic retinopathy at Aflibercept administration with control. Method: This is a prospective experimental study with post-test with control design. Subjects were taken from 24 eyes from 24 patients, who came to dr. Kariadi General Hospital and National Diponegoro Hospital between March until September 2016. Subjects were divided into the patient with Aflibercept administration and control. Study variables in this study are Placenta Growth Factor levels in the vitreous in the patient with diabetic proliferative retinopathy. Measurements of PlGF levels with ELISA methods are conducted at GAKI Laboratory, Medical Faculty, Diponegoro University. This data tested for normality used with Saphiro Wilk, and homogeneity variance with Lavene and test hypothesis used with Mann Whitney. Results: Sample of this study are 24 patients proliferative diabetic retinopathy, twelve are the control group, and twelve are Aflibercept group. Average levels of PlGF in the control group are 263,97 pg/ml + 354,98 SD, with minimum value 12,19 pg/ml and maximum value 1002,00 pg/ml. Average levels of PlGF in the treatment group are 92,84 pg/ml + 9,54 SD, with minimum value 76,45 pg/ml and maximum value 112,30 pg/ml. Hypothesis test results obtained significance value 0,488. Conclusion: There was no significant difference between PlGF levels in the control group and the treatment group.